A Method of Plan and Design for Integrated Energy System of Industrial Park - GAO Shoucong; LIU Lu; ZANG Xiaodi (Kongzhi Yu Xinxi Jishu)
There are many kinds of distributed energy technologies in a park type integrated energy system. In the design of a distributed energy system, it is necessary to consider not only different modes such as merging and off grid, but also various factors such as user demand, equipment investment cost, operation economy, etc., which makes the plan and design of the system difficult and time-consuming. Aiming at the plan and design of distributed equipment in park type integrated energy system, this paper established a quasi steady state model of typical distributed generation, a quasi steady state model of typical cooling / heating equipment, and a quasi steady state model of general electric energy storage device. An optimization strategy with the lowest economic operation cost as the single objective was used to construct the single objective scheduling optimization model of integrated energy system, and a plan and design software was applied. The software carried on the simulation calculation to the project case, obtained the optimal result of system equipment plan and design suitable for this project. After the project is simulated by planning software, the average calculation time is about 15 minutes (in the traditional method, technicians need to spend several days for data processing and analysis in the early stage), which improves the project planning efficiency by more than 50% and can help customers quickly evaluate and select high-quality projects.